Implementasi Keikutsertaan Masyarakat Dalam Musyawarah Perencanaan Pembangunan Daerah Di Kabupaten Bima - Firmansyah, Firmasnyah; Budiman, Arif; Rizkiani, Firliah (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
The implementation of mandatory affairs in the implementation of local autonomy (OTODA) in Article 150 of Law No. 23 of 2014 concerning Regional Governments. The mandatory affairs referred to are development planning affairs. Development planning, as implemented in Sape District through the Musrenbang activity. The participatory meetings conducted by the community of Sape District begin with village-level deliberations (musbangdes), which then continue to the district-level Musrenbang. The aim of this research is to describe and analyze the process, community participation, as well as inhibiting and driving factors in the district Musrenbang activity. This research method is descriptive research with a qualitative approach, using interactive model qualitative data analysis. The research findings prove that community participation in the Sape District Musrenbang is present and active. In this phenomenon, there is synergy between the government and the community in the development planning program in Sape District.